Pendapatan Usahatani Jagung Di Desa Tumani Selatan Kecamatan Maesaan Kabupaten Minahasa Selatan - Panelewen, Elisa; Laoh, Olly Esry Harryani; Sondakh, Mex Frans Lodwyk (Sam Ratulangi University, 2023)
This study aims to calculate corn farming income in Tumani Selatan Village, Maesaan Sub-district, South Minahasa Regency. The research was conducted from June to July 2023. Sampling using sample survey method with 16 farmers as respondents. The data used in this study are primary data and secondary data and use income analysis calculations. Data analysis used in this research is quantitative descriptive analysis in determining production, revenue and income. The results showed that the average revenue of corn farmers per hectare in South Tumani Village, Maesaan Subdistrict, South Minahasa Regency in one harvest was IDR16.588.090. The average income of corn farmers per hectare amounted to IDR8.537.786.